Confluences between poetry and photography in “Auto-retrato”, by Laís Corrêa de Araújo (Research, Society and Development, 2020)
This researcg, of an essentially qualitative nature, aims to provoke reflections on the confluences existing between poetic and photographic making. Therefore, it takes as a base a text by the modern writer Laís Corrêa de Araújo, which is the poem “Auto-retrato”, extremely significant to think about the connections between these two sign modalities - photography and poetry, as complex instruments of immobilization of the instant that problematize the complex temporal tension that encloses past and present, as well as the question of perception, representation, reflection and refraction of the reality. Hereupon, photographic image and poetic word are amalgamated as two forms of representation that merge and become transfigured into a photographic word and poetic image, in order to allow the glimpse of the “behavior” of the image before a subjective perspective, constructed and, therefore, manipulable, both in verbal and light writing.